الصمود النفسي ومعنى الحياة والتدفق من وجهة نظر علم النفس الإيجابي دراسة تحليلية لصمود الجيش العربي السوري - سليمون, ريم (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
Psychological resilience refers to the individual’s tendency to remain steadfast and composed in time of adversity and pressure in addition to his ability to be actively compatible and to cope positively with traumatic states and pressures.Consequently, this is conducive to fastness in recovery and overstepping traumatic states. It also leads to the previous normal functional state, and therefore to considering the traumatic or pressing state an opportunity to empower and fortify one’s self against traumatic states and pressures in the future. The “Meaning of Life,” as an idiom, is considered one of the concepts that has attracted the interest of researchers in the field of mental health. For the human being, the meaning of life relates to its value, his self-contentment and his self-appreciation in the sense that his life revolves around and within the role that he finds himself best in acting.Frankl(1974) asserts that the meaning of life, love and identity follows the traumatic experiences that the individual encounters through his life. Bad situations are considered an opportunity for the individual to grow. To achieve this, one must have faith in the future, and without faith, there is no meaning for life or reason for living. The flow state represents the crucial factor in constituting the meaning and goal of life, and making sense and value out of it. Hence, this state pushes those who cope up with it to be creative; nay, to the highest degrees of human creativeness. This paper attempts to link the previous variables with the resilience of the Syrian Arab Army by approaching methodologically the elements of this research paper. This methodological approach depends on analyzing the literature of the subject matter by collecting and coordinating the theoretical writings and research studies in this domain, then analyzing them in order to illustrate their underlying implications, and therefore easing the task to know the secret of psychological resilience, flow, and meaning of life within the context of positive psychology. In order to excavate for this secret, one must look for the nature of these variable and its limitations, and applying them on the resilience of the Syrian Arab Army. Thus, the current paper relies on a description and explanation emanating from building a base of concepts, and the methodology here is closer to qualitative research. يهدف البحث الحالي إلى دراسة العلاقة بين عدة مفاهيم أساسية, تعكس مكامن القوة والضعف في الشخصية الإنسانية ومالها من دور مؤثر على الواقع النفسي والمادي للفرد, وهي الصمود النفسي ومعنى الحياة والتدفق من وجهة نظر علم النفس الإيجابي.ويشير مفهوم الصمود النفسي إلى فكرة ميل الفرد إلى الثبات والحفاظ على هدوئه عند التعرض لضغوط أو مواقف عصيبة, فضلاً عن قدرته على التوافق الفعال والمواجهة الإيجابية لهذه الضغوط وتلك المواقف الصادمة, وبالتالي سرعة التعافي والتجاوز السريع للموقف الصادم, والعودة إلى الحالة الوظيفية العادية, واعتبار الموقف الصادم أو الضاغط فرصة لتقوية الذات وتحصينها ضد الضغوط والمواقف الصادمة مستقبلاً.وتحاول الورقة الحالية ربط المتغيرات السابقة بصمود الجيش العربي السوري, من خلال التناول المنهجي لعناصر الورقة البحثية الحالية, الذي اعتمد على تحليل أدبيات المجال, من خلال تجميع وتنسيق الكتابات النظرية والدراسات البحثية في المجال, وتحليلها, بهدف توضيح مضامينها بما يسهم في الكشف عن ماهية الصمود النفسي والتدفق ومعنى الحياة في سياق علم النفس الإيجابي من خلال الكشف عن طبيعة هذه المتغيرات ومحدداتها وتطبيق ذلك على صمود الجيش العربي السوري, وتستند الورقة الحالية على الوصف والتفسير المنطلق من بناء قاعدة مفاهيم, وهي منهجية أقرب إلى البحث الكيفي.وخلصت البحث الحالية إلى أهمية العلاقة بين هذه المتغيرات, وتم تحديد أهم ثمرات الصمود النفسي ومقوماته, وأهم خصائص الأشخاص ذوي الصمود النفسي